Seafood "Gardens" - Williams, Jim (Waka Kuaka, 2016)
This article reviews seafood gardening by Ngāi Tahu, including seeding, habitat enhancement, species improvement and marine storage. It is argued that a regime of management practises certainly justifies the term "gardening" as has been argued for similar practises elsewhere (in particular, the American Pacific coast).